Harmonization of National and International Law in the Utilization of AI for the Organization of Hajj A Collaborative Study Between the Governments of Indonesia and Saudi Arabia in Hajj Technology Systems - Aljawi, Muhammad Farid; Santiago, Faisal (Greenation Publisher & Yayasan Global Resarch National, 2025)
The annual Hajj pilgrimage presents significant logistical challenges, increasingly addressed through Artificial Intelligence (AI) by the Kingdom of Saudi Arabia, often in collaboration with countries like Indonesia, which sends the largest contingent of pilgrims. This study examines the complex legal landscape surrounding the use of AI in Hajj organization, focusing on the need for harmonization between Indonesian national law (including Law No. 27/2022 on Personal Data Protection and Law No. 8/2019 on Hajj/Umrah), Saudi Arabian law (including the Personal Data Protection Law and SDAIA AI guidelines), and relevant international frameworks (AI ethics, data protection, human rights). Using a qualitative methodology based on secondary data analysis, this paper identifies key AI applications in Hajj, analyzes existing Indonesia-Saudi collaborative efforts, and evaluates points of conflict and convergence between the respective legal regimes. Findings highlight significant challenges in areas such as cross-border data transfer, sensitive data processing, algorithmic bias, and accountability. The study concludes by recommending pathways towards legal harmonization to ensure ethical, rights-respecting, and efficient AI deployment in managing the Hajj, fostering continued collaboration between Indonesia and Saudi Arabia.